Kurang Energi Kronis Ibu Hamil sebagai Faktor Risiko Bayi Berat Lahir Rendah - Virdaus Syarifuddin Muhammad Hakimi Berty Murtiningsih (Berita Kedokteran Masyarakat (BKM), 2011)
Background: Infants of low birth weight (LBW) is associated with high infant mortality rate. In 2009 the infant mortality rate in the Bantul district reached 11.49 per 1000 KH of which 36.6% are caused by low birth weight. Chronic Energy Deficiency (CED) and maternal age are risk factors for the dominant cause of LBW in 2009.Objectives: To know the description of the case of CED, LBW and the magnitude of the risk of CED on the incidence of LBW in Bantul district.Methods: The study design is Matched case-control study. The study population was the mother who gave birth during the year 2010 and 2011, the study site sub-divided based on the cluster. The case is the mother who gave birth to babies with weight <2500 grams, the control is the mother who gave birth to a baby weighing > 2500 grams. Large sample of cases was 149 people, with a 1:1 ratio of cases and controls were then obtained a total sample of 298 people. Sampling controls through matching on parity and maternal age. The data obtained were analyzed by univariate, bivariate and multivariable, then presented in tables and graphs.Results: In multivariable analysis, there are two significant variables related to LBW: CED (OR = 3.95; 95% CI = 2.147 to 7.299, p <0.001) and anemia (OR = 3.17; 95% CI = 1.660 to 6.051; p <0.001).Conclusion: CED was suffer from 69,1% respondents. Mother who gave birth to babies with LBW, 83,2% suffer from CED and 94,6% lack of iron intake. Pregnant women with CED-risk gave birth to babies with LBW. Pregnant women who suffer from CED and anemia predicated 75.53% will give birth to babies with LBW.Keywords: KEK, low birth weight, matched case control study